2016
DOI: 10.1109/tit.2016.2523980
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Algorithms for the Data Exchange Problem

Abstract: Abstract-In this paper we study the data exchange problem where a set of users is interested in gaining access to a common file, but where each has only partial knowledge about it as side-information. Assuming that the file is broken into packets, the side-information considered is in the form of linear combinations of the file packets. Given that the collective information of all the users is sufficient to allow recovery of the entire file, the goal is for each user to gain access to the file while minimizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
103
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(109 citation statements)
references
References 36 publications
6
103
0
Order By: Relevance
“…minimum) weighted cost, the corresponding rate vector, and packet index vectors. The complexity of our algorithm is bounded by O(N 3 K 3 log(K)) 1 , which is the same as the complexity of the best-known algorithm for basic CDE problem and significantly lower than the algorithms proposed in [11], [6], [12].…”
Section: B Contributionsmentioning
confidence: 84%
See 4 more Smart Citations
“…minimum) weighted cost, the corresponding rate vector, and packet index vectors. The complexity of our algorithm is bounded by O(N 3 K 3 log(K)) 1 , which is the same as the complexity of the best-known algorithm for basic CDE problem and significantly lower than the algorithms proposed in [11], [6], [12].…”
Section: B Contributionsmentioning
confidence: 84%
“…A randomized algorithm was proposed to estimate the minimum number of required transmissions [5]. Deterministic algorithms based on Dilworth Truncation optimization were proposed to compute the exact minimum number of required transmissions [3], [4], [6]. It has been recently shown that a deterministic algorithm based on conditional basis construction [1] can solve this optimization problem with lower complexity.…”
Section: A Related Workmentioning
confidence: 99%
See 3 more Smart Citations